The Influence of Advertising and Trust on Marketplace Purchase Decisions and Their Impact on Repurchase Intentions of Gen Z Students in Madiun City - Fredy Susanto; Ina Syarifah (Brilliant International Journal Of Management And Tourism, 2025)
In the current digital era, information is readily available using digital technology. Economic activities are also facilitated by the digital economy. E-commerce is one such digital economic activity. The growth trend of e-commerce continues to increase annually. This expansion is driven by the emergence of various online buying and selling sites or marketplaces, which positively influence the high level of internet usage and spur the development of e-commerce in Indonesia. This study aims to examine the influence of advertising and online trust on marketplace purchase decisions. It also aims to examine how online advertising and trust in marketplaces influence Gen Z's repurchase intentions. The study used a quantitative method, as an explanatory research within a field survey. The sample size was 150 respondents. Data analysis was performed using the Partial Least Squares (PLS) method using SmartPLS version 3 software. PLS is a Structural Equation Modeling (SEM) method that is superior to other SEM techniques. The results of this study indicate that advertising has a significant positive effect on purchasing decisions and repurchase intentions. Further research indicates that trust has a positive and significant effect on both purchasing decisions and repurchase intentions. In this study, purchasing decisions also showed a positive and significant effect on repurchase intentions.